On the Directions of Scientific and Technical Development of the Republic of Belarus - Sikorskaya, O. N.; Bovkunovich, M. A. (Scientific and technical information processing, 2019)
— On the basis of the Scopus database, an analysis of publications of Belarusian scientists in individual fields of science was carried out, which made it possible to identify the specialization and main areas of scientific work in the Republic of Belarus and determine the country’s place in the global scientific process.